By elimination:
y = 3x - 1
y = 2x + 2
Subtract the second equation from the first
0 = x - 1
y = 2x + 2
Subtract the first equation from the second
0 = x - 1
y = x + 3
Subtract the first equation from the second again
0 = x - 1
y = 4
Subtract x from both sides of the first equation
- x = - 1
y = 4
Divide the first equation by (-1)
x = 1
y = 4
<h3>
So, the solution is x = 1 and y = 4 {or: (1, 4)}</h3>
You can but it isnt really a good idea to do that if you want full credit
Combine like terms for 30c +3d
Answer:
98.42
Step-by-step explanation:
7 × 14.6 =
= 7 × (7 + 7 + 0.6)
= 7 × 7 + 7 × 7 + 7 × 0.6
= 49 + 49 = 0.42
= 98.42
Answer:
You have to find the inches then you have to either add or subtract them.
Step-by-step explanation: